How Waqf Solves Backlogs - Anita Priantina; Munira Pratiti Satriyasyifa (Tazkia Islamic Finance and Business Review, 2021)
The gap between demand and affordable supply has led to a housing backlog, especially in Indonesia. Solution is needed, especially to provide housing for low-income earners. This study discusses the potential for implementing a new financing scheme that combines Sukuk Linked Waqf, Cash Waqf Linked Sukuk, CSR, and non-halal funds for housing development in the long-term using the Benefit, Opportunities, Cost and Risk-Analytical Network Process (ANP-BOCR) method. The results of this study indicate that under this alternative scheme, the benefits and opportunities for all parties involved in housing development outweigh the costs and risks. Therefore, the combination of SLF and CWLS has significant potential to solve backlog problem in Indonesia. Keywords: